Critical Pedagogy in Online Social Work Education: Changing Conceptions of Time in the Neoliberal University. (April 2020) - Smith, Kristin; Jeffery, Donna; Collins, Kim
Abstract : Neoliberal universities embrace the logic of acceleration where the quickening of daily life for both educators and students is driven by desires for efficient forms of productivity and measurable outcomes of work. From this perspective, time is governed by expanding capacities of the digital world that speed up the pace of work while blurring the boundaries between workplace, home, and leisure. In this article, we draw from findings from qualitative interviews conducted with Canadian social work educators who teach using online-based critical pedagogy as well as recent graduates who completed their social work education in online learning programs to explore the effects of acceleration within these digitalised spaces of higher education. We view these findings alongside French philosopher Henri Bergson's concepts of duration and intuition, forms of temporality that manage to resist fixed, mechanised standards of time. We argue that the digitalisation of time produced through online education technologies can be seen as a thinning of possibilities for deeper and more critically self-reflexive knowledge production and a reduction in opportunities to build on social justice-based practices.